(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The rise of social media and online news platforms has transformed public interaction, making comments a vital indicator of public sentiment towards political figures. Specific Background: This study focuses on the negative news and hate speech surrounding presidential candidates Prabowo Subianto and Gibran Rakabuming Raka during the 2024 Presidential Election, particularly in the comment sections of Metro TV News. Knowledge Gap: Despite the significance of social media interactions in shaping public perception, limited research has explored how negative news and hate speech influence public views of political candidates in this context. Aims: This study aims to analyze the impact of negative news and hate speech regarding Prabowo and Gibran in the comment section of Metro TV News’ YouTube channel. Results: Utilizing a qualitative descriptive method, the findings reveal that public perception of Prabowo and Gibran is significantly affected by negative comments and hate speech, reflecting broader societal controversies surrounding their candidacy. Novelty: This research provides a comprehensive analysis of how digital comment sections contribute to public discourse about political figures. Highlights: • Social media comments are crucial indicators of public sentiment. • Public perception is significantly influenced by negative comments and hate speech. • Research underscores the need for effective media policies regarding online interactions. Keywords: Negative News, Hate Speech, Public Sentiment, Political Candidates, Social Media